The Treatment of Linear and Narrow Scar after Craniotomy Using the Follicular Unit Excision - Okochi, Hiromi; Onda, Masamitsu; Momosawa, Akira; Okochi, Masayuki (Archives of Plastic Surgery, 2022)
Background The scar alopecia after cranioplasty (SAC) may decrease the patient's quality of life. We have treated SAC using follicular unit extraction (FUE). The aim of this study was to discuss that efficacy of FUE and how much hair follicular unit (FU) should be transplanted intraoperatively for the treatment of SAC.Methods We treated 10 patients (4 men and 6 women) who had SAC using FUE.Results The average age, alopecia size, and intraoperative hair density on the graft area were 29.8 ± 12.1 years, 29.8 ± 44.5 cm2, and 34.6 ± 11.8 FU/cm2, respectively. One year postoperatively, the average hair survival rate on the graft area was 66.3 ± 6.1%. Hair appearance was rated as good in six, fair in three, and poor in one. Among patients whose 1-year postoperative hair density was ≥ 20 FU/cm2, five of six patients achieved good results. However, among patients whose 1-year postoperative hair density was < 20 FU/cm2, all four patients achieved fair or poor results. The postoperative hair density was significantly higher in patients whose 1-year postoperative hair density was ≥ 20 FU/cm2 than in patients whose 1-year postoperative hair density was < 20 FU/cm2. The rate of achieving fair or poor results was significantly higher if the postoperative hair density was < 20 FU/cm2 than if it was ≥ 20 FU/cm2 (p = 0.047).Conclusions FU excision is useful for the treatment of scar alopecia after craniotomy. Our results suggest that the 1-year postoperative hair density should exceed 20 FU/cm2 to achieve good outcomes.
Keywords: hair restoration; craniotomy; scar alopecia; follicular unit extraction